FENOMENA PERNIKAHAN DINI DI KOTA SERANG DAN IMPLIKASINYA TERHADAP HUKUM PERKAWINAN DI INDONESIA - Queencyla Rifani Putri; Fitria Agustin (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the phenomenon of early marriage in Serang City and its implications for marriage law in Indonesia. This issue is significant because early marriage not only affects social and economic aspects but also creates complex legal consequences, particularly regarding the validity of marriage, the legal status of families, and the effectiveness of existing regulations. This research employs a normative juridical method with statutory and conceptual approaches, supported by relevant literature studies. The findings indicate that early marriage in Serang City is influenced by various factors, including economic conditions, low levels of education, and strong socio-cultural norms. The impacts include increased school dropout rates, the perpetuation of intergenerational poverty, and a decline in the quality of human resources. From a legal perspective, although regulations regarding the minimum age of marriage have been established, the practice of marriage dispensation demonstrates a gap between legal norms and social reality. Furthermore, early marriage has implications for family legal status, including the position of children and other civil rights. Therefore, comprehensive efforts are required through strengthening regulations, increasing public awareness, and empowering education and the economy to reduce early marriage rates and improve the effectiveness of marriage law in Indonesia.